A computational study of the inclusion of β‑cyclodextrin and nicotinic acid: DFT, DFT‑D, NPA, NBO, QTAIM, and NCI‑RDG studies - Houdhaifa R. Belhouchet; Tahar Abbaz; Amel Bendjedou; Abdelkrim Gouasmia; Didier Villemin (Journal of Molecular Modeling, 2020)
Forming complexes with cyclodextrins can protect nicotinic acid (vitamin B3) from premature metabolism and enhance the solubility and stability of this drug. In this work, the formation of the inclusion complex of the neutral form of nicotinic acid and β-cyclodextrin was achieved. The complex is modeled using PM3, PM6-D4H3, and PM7, by considering two orientations of the guest: A and B, one is from wide to narrow rim, and the second is from narrow to the wide rim ,respectively. The global minima positions were re-optimized using three density function methods: MN-15, B3LYP, and PW6B95-D3 with polarized Pople basis set 6-31G(d) in gas and aqueous phase. Orientation A showed the minimum complexation energy where the carboxylic functional group of nicotinic acid is located on the primary hydroxyl rim of β-cyclodextrin and the pyridine ring is totally embedded in the cavity. To further our study on the nature of complexation and the interactions of this host–guest system, different calculations were done. The reactivity indices showed that orientation A is harder than B and more electrophilic; the charge transfer occurred from the host to the guest and was confirmed by the natural population analysis (NPA). The natural bond orbitals (NBO) reveal the delocalization of orbitals between the host and the guest, quantum theory of atoms in molecules (QTAIM) analysis, and non-covalent interaction (NCI) analysis based on a reduced density gradient (RDG) give a detailed description of the nature of interactions between the host and the guest such as the hydrogen bonding and van der Waals interaction, and confirmed the stability of the complex given by the orientation A.